Inline mechano-vibration holography for simultaneous phase and elasticity mapping of soft samples - Abdioglu, Hasan Berkay; Isik, Yagmur; Sevgi, Merve; Caglar, Esmahan; Esmer, Gokhan Bora; Uvet, Huseyin; Demircali, Ali Anil (Optica Publishing Group, 2026)
Off-axis holography enables single-shot phase retrieval but reduces spatial bandwidth, while in-line phase-shifting interferometry preserves bandwidth yet requires reference-path stepping and is sensitive to drift, limiting dynamic measurements. Moreover, viscoelastic mapping is rarely available from the same holographic measurement. We propose vibration-encoded in-line Mach-Zehnder holography for simultaneous thickness and viscoelasticity mapping of soft samples. Twelve holograms acquired over one vibration cycle are analyzed using Besselbased harmonic inversion and robust regression to recover the static phase, modulation depth, and phase lag, yielding thickness and Kelvin-Voigt storage and loss modulus maps (E ', E ''). Simulations recover E ' and E '' to within similar to 2% across a wide E ''/E ' range and achieve sub-micron thickness error over 20-45 & micro;m beads. Experiments on calibrated polyacrylamide beads show sub-micron thickness repeatability (median similar to 0.57 & micro;m over 40 repeats) and stiffness estimates typically within 10% of ground truth, and we further demonstrate the approach on adherent MCF-7 cells.
Keywords: Biochemistry & Molecular Biology; Optics; Radiology, Nuclear Medicine & Medical Imaging